Understanding the post-Archaic population of Satricum, Italy: A bioarchaeological approach. (June 2020) - Sengeløv, Amanda; van de Wijdeven, Giswinne; Snoeck, Christophe; Laffoon, Jason; de Hond, Rens; Gnade, Marijke; Waters-Rist, Andrea
Highlights: Elemental (Sr) and isotope (Sr, C & O) analyses were performed. Dental non-metric traits were assessed. All individuals appear to be local. A difference in strontium concentrations is seen. Two intersecting graves are spatially and possibly biologically related. Biodistance analysis suggests the necropoleis contain different gene pools. Abstract: This paper contributes to the current debate regarding the ethno-cultural identity and origins of the post-Archaic (5th to 4th centuries BCE) population of the town of Satricum by introducing bioarchaeologial data including strontium isotope ratios, strontium concentrations, δ 13 C and δ 18 O values of tooth enamel, as well as dental morphological traits. Previous studies suggested a change in the original Latin population of ancient Satricum as a result of migrating groups called the Volscians coming from the eastern mountainous hinterland of Latium. The purportedly relatively short occupation of Satricum (ca. 150 years) by the Volscians during the post-Archaic period increases the chance of identifying the first generation of migrants coming from the mountains. Individuals from three presumable Volscian necropoleis in Satricum are analyzed. Forty-three third molars were sampled for isotope and elemental analyses. All individuals appear to be "local" based on their strontium and oxygen isotope ratios. However, three individuals have statistically lower strontium isotope ratios than the rest, two of which originate from two intersecting graves. These two also have the lowest strontium concentrations, potentially suggesting they are spatially and possibly biologically related. At the group level, the strontium concentration data show a clear difference between the necropoleis. An additional difference is in the dental non-metric trait frequencies, with a biodistance analysis suggesting the necropoleis contain different gene pools (MMD score of 0.789). It is hard to determine if these data suggest (1) a population that experienced fast and marked gene flow between use of the necropoleis, or (2) a population with large, distinct kin groups using different necropoleis. Nonetheless, the data show that the 5th to 4th century BCE was a period of change in Satricum and this work paves the way for future research as we strive to understand the origins and identities of these peoples.